Legal regulation of the status of a teacher in international acts and legislation of foreign countries - Abdakimova, D.A. (Bulletin of the Karaganda University “Law Series”, 2023)
The article is devoted to the analysis of the legislative regulation of the status of a teacher in various legal systems and international law. In particular, universal and regional specialized acts in the field of fixing the status of a teacher and his social guarantees, as well as the features of such regulation in some foreign legal systems are considered. The author in his scientific study analyzes the international acts of the United Nations, the International Labor Organization, UNESCO in the field of registration of the teacher’s status. Particular attention is paid to the countries whose education systems occupy leading positions in the ranking of countries: Finland, China. The Finnish education system occupies a leading position in terms of the level of school education, the experience of which is analyzed by the world educational community as a “Finnish phenomenon”. A scientific study of the teacher’s status was carried out using data from international ratings, such as the Global Teacher Status Index, PISA (Programme for International Student Assessment). The author focuses on the activities of independent professional associations for the protection of teachers’ rights in foreign countries and their role in strengthening the status, providing social guarantees, and protecting rights. A critical analysis of the principles of the activities of the Kazakhstan Branch Trade Union of Educational and Scientific Workers for compliance with its generally accepted standards of the International Trade Union Confederation has been carried out. The article assesses the law of the Republic of Kazakhstan “On the status of a teacher” from the position of compliance not only with international law standards, but also with the requirements of modernity